Persistent Polyclonal B Cell Lymphocytosis B Cells Can Be Activated through CD40-CD154 Interaction - Emmanuelle Dugas-Bourdages; Sonia Néron; Annie Roy; André Darveau; Robert Delage (Advances in Hematology)
Persistent polyclonal B cell lymphocytosis (PPBL) is a rare disorder, diagnosed primarily in adult female smokers and characterized by an expansion of CD19+CD27+IgM+ memory B cells, by the presence of binucleated lymphocytes, and by a moderate elevation of serum IgM. The clinical course is usually benign, but it is not known whether or not PPBL might be part of a process leading to the emergence of a malignant proliferative disorder. In this study we sought to investigate the functional response of B cells from patients with PPBL by use of an optimal memory B cell culture model based on the CD40-CD154 interaction. We found that the proliferation of PPBL B cells was almost as important as that of B cells from normal controls, resulting in high immunoglobulin secretion with in vitro isotypic switching. We conclude that the CD40-CD154 activation pathway is functional in the memory B cell population of PPBL patients, suggesting that the disorder may be due to either a dysfunction of other cells in the microenvironment or a possible defect in another B cell activation pathway.